Prescribed time backstepping sliding mode control for attitude stabilization of plant-protection UAVs under wind and motor disturbances - Zhu, Chenqi; Wang, Zhikai; Zhang, Dongkai; Si, Pengju (Frontiers in Plant Science, 2025)
In this paper, a novel prescribed time convergent backstepping sliding mode control method for robust attitude stabilization of plant-protection UAV is proposed to solve the uneven pesticide spraying issue caused by strong gusts and motor dynamics. Firstly, a mathematical model of the plant-protection UAV with disturbance is established, which regards the gust and the dynamic characteristics of the motor as the total disturbances of the system. Secondly, a prescribed time extended state observer is proposed to accurately estimate the error. Subsequently, an integral sliding surface is proposed on which the states converge to the origin in prescribed time. Moreover, a prescribed time control method is proposed by combining the variable coefficient exponential approach law and the observer. Finally, the stability of the algorithm is verified by the Lyapunov functions. The numerical simulation results show that under different initial states, this method can achieve attitude stability in preset time, which provides a guarantee for the uniform spraying of the plant-protection UAVs.